(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article presents the results of research conducted to determine the effect of different carrot cultivation methods on product quality and yield. The study showed that mulching carrot crops with a glauconite-humus mixture in a 1:1 ratio resulted in the highest product quality and yield. The use of a humus-glauconite mixture in a 1:1 ratio increased yield by 7.9 t/ha, or 35.7%, compared to the control treatment.